Mobilizing the organization : bringing strategy to life - Lutwin, George (Prentice Hall HertfordshireGB, 1996)
Examines the 4 strategic change processes that have been used by top management teams. Identifies these processes as: PURPOSE, which gives meaning to work; INFRASTRUCTURE which embodies the understandings and commitments that are needed to make the structure work; GUIDANCE STSTEMS which provide front-end direction and back-end control; and RESOURCING, which is, identifying the best persons for jobs, preparing, and moving them on etc.